Some problems of the robot control based on using changeable structures (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 1996)
For antropomorphic robots a compact system of differential equations is obtained. The solutions are applicable for control purposes. The new approac improves the possibilities of the adaptive robot control systems.